PELATIHAN ABON AYAM PEDAS: INOVASI PENGOLAHAN HASIL PERTANIAN CABAI DI DESA MANDIRO, TEGAL AMPEL, BONDOWOSO - Sarifah, Lailatul; Arvito Caesario Arifianto Putra; Trivani Yuniar Baharini; Dimitry Febri Damayanti; Dimas Dwi Santoso; Aldo Wijaya; Khalifah Anggun Lestari; Enggita Anggraeni Okta; Muhammad Fatchur Rozi; Sofia Salsabila (Jurnal Bakti Masyarakat Indonesia, 2024)
Economic growth plays a crucial role in fostering the development of a economically advanced nation. Economic growth is also one of the key points in the Sustainable Development Goals (SDGs), specifically Goal 8 (Decent Economic Growth). However, economic growth in Indonesia is still not considered substantial, as there are disparities in rural economic growth, one of which is evident in Bondowoso Regency, particularly in Mandiro Village, Tegalampel District. Despite the significant potential in Mandiro Village, its resources have not been fully harnessed and improved to achieve enhanced economic conditions. One of the potential areas for improvement lies in agriculture, as the village possesses vast agricultural land which serves as the primary livelihood for the local community. The main agricultural product is chili peppers, which can be processed into valuable products for both the local village population and the wider society. These chili peppers are planned to be processed into a special spicy chicken floss known as the signature chili-infused chicken floss of Mandiro Village. This endeavor will be facilitated through training organized by the KKN UNEJ (Community Service Program of the University of Jember) Group 98, situated within Mandiro Village, with a particular focus on engaging the village residents, especially the women. The aspiration stemming from this training initiative is that the community will be motivated and enthusiastic to engage in entrepreneurship by harnessing the chili pepper yields of Mandiro Village. This innovative product, the spicy chicken floss, holds the potential to enhance the village's economy by augmenting the income of its inhabitants. ABSTRAK Pertumbuhan ekonomi memegang peranan penting dalam mendorong terwujudnya negara yang maju dalam sisi perekonomian. Suatu daerah dapat dikatakan sebagai daerah yang maju apabila memiliki tingkat pertumbuhan ekonomi yang terus meningkat. Pertumbuhan ekonomi juga menjadi salah satu poin dalam Sustainable Development Goals (SDGs) yakni poin ke 8 (Pertumbuhan Ekonomi Desa Merata). Akan tetapi, pertumbuhan ekonomi di Indonesia masih belum bisa dikatakan meningkat karena masih terdapat pertumbuhan ekonomi desa yang belum merata, salah satunya terjadi di Kabupaten Bondowoso, tepatnya di Desa Mandiro, Kecamatan Tegalampel. Padahal, potensi yang ada di Desa Mandiro sangat mumpuni untuk dikelola dan ditingkatkan agar dapat mewujudkan perekonomian yang meningkat. Salah satu potensi yang dapat ditingkatkan yaitu dari segi pertaniannya karena lahan pertanian di desa ini sangat luas dan menjadi mata pencaharian utama masyarakat setempat. Hasil pertanian utama yakni berupa cabai yang akan diolah menjadi produk atau olahan yang bermanfaat, baik untuk masyarakat desa setempat maupun masyarakat luas. Cabai ini nantinya akan diolah menjadi abon ayam pedas spesial cabai khas Desa Mandiro dengan memfokuskan pengadaan pelatihan oleh KKN UNEJ kelompok 98 yang ada di Desa Mandiro kepada masyarakat desa, khususnya ibu-ibu. Harapan dari hasil pelatihan ini yakni masyarakat mau dan gemar berwirausaha dengan memanfaatkan hasil pertanian cabai Desa Mandiro berbentuk inovasi produk abon ayam pedas yang dapat meningkatkan perekonomian desa melalui peningkatan penghasilan masyarakatnya.